CREATING FIRM VALUE: LINKING DEMAND UNCERTAINTY, ADAPTATION VERSUS REPLACEMENT INVESTMENTS, AND RISK - Nur Khusniyah Indrawati (Fakultas Ekonomi dan Bisnis Universitas Padjadjaran, 2020)
Real assets investment can relate to real options. This study aims at analysing the effect of demand uncertainty on replacement investment and adaptation investment supported by manager’s attitude towards risk and the effect of each investment type on firm values. The 352 observation data was collected from companies listed in Indonesia Stock Exchange. The data was analyzed using Path analysis. The research findings prove that demand uncertainty can increase the adaptation investment, which is in contrast to replacement investment. The manager’s attitude towards risk in terms of demand uncertainty and adaptation investment is considered as risk-taker, while in replacement investment is risk aversion. The effects of the two investment types also differ on firm value. The adaptation investment cannot increase the firm value, while the replacement investment can. The manager has the policy to make or not to make profitable investments to maximize investment returns based on real option policy and to decrease the risk, as the real assets investments are not passive investments. The manager’s attitude towards risk is quasi moderation, both in replacements investment and adaptation investment. It implies that manager’s attitude towards risk can be a moderator and independent variable.